Cote d'Ivoire : Sixth Review Under the Extended Credit Facility Arrangement and Requests for Waiver of Nonobservance of Performance Criterion, Augmentation of Access, and Twelve-Month Extension of the Current Arrangement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
All end-June performance criteria and indicative targets under the ECF arrangement were met, and all structural benchmarks were completed, albeit with minor delays. However, there was a nonobservance of the continuous performance criterion on the ceiling on new nonconcessional external debt in July with the issuance of the USD 750 million Eurobond (exceeding the USD 500 million program ceiling).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet